Phylogeography of Heliconius cydno and its closest relatives: Disentangling their origin and diversification (2014)
The origins of the extraordinary diversity within the Neotropics have long fascinated biologists and naturalists. Yet, the underlying factors that have given rise to this diversity remain controversial. To test the relative importance of Quaternary climatic change and Neogene tectonic and paleogeographic reorganizations in the generation of biodiversity, we examine intraspecific variation across the Heliconius cydno radiation and compare this variation to that within the closely related Heliconius melpomene and Heliconius timareta radiations. Our data, which consist of both mtDNA and genome-scan data from nearly 2250 amplified fragment length polymorphism (AFLP) loci, reveal a complex history of differentiation and admixture at different geographic scales. Both mtDNA and AFLP phylogenies suggest that H. timareta and H. cydno are probably geographic extremes of the same radiation that probably diverged from H. melpomene prior to the Pliocene-Pleistocene boundary, consistent with hypotheses of diversification that rely on geological events in the Pliocene. The mtDNA suggests that this radiation originated in Central America or the northwestern region of South America, with a subsequent colonization of the eastern and western slopes of the Andes. Our genome-scan data indicate significant admixture among sympatric H. cydno/H. timareta and H. melpomene populations across the extensive geographic ranges of the two radiations. Within H. cydno, both mtDNA and AFLP data indicate significant population structure at local scales, with strong genetic differences even among adjacent H. cydno colour pattern races. These genetic patterns highlight the importance of past geoclimatic events, intraspecific gene flow, and local population differentiation in the origin and establishment of new adaptive forms. © 2014 John Wiley and Sons Ltd.